Parent attachment, peer attachment and depression among adolescents in Selangor - Arshat, Zarinah; Wong, Yoke Lee (Panoply Consultancy, 2017)
This study aims to determine the relationship between parent and peer attachment with depression among adolescents in Selangor. A total of 402 adolescents were recruited using multistage cluster random sampling technique in Selangor. The measurements of parent and peer attachment, and depression were adopted from Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1987) and Beck Depression Inventory Second Edition (Beck, Steer, & Brown, 1996). The findings of the study demonstrated that higher parent attachment and peer attachment were associated with lower depression among adolescents. Findings showed that male adolescents had higher level of peer attachment compared to female adolescents. The analysis findings of this study contributed crucial implications for the parents, adolescents, educators, and future researchers to understand the importance of knowledge on depression by identifying the root cause of problems and provided appropriate ways to solve the problem of depression. Future research has to carry out continually and consistently by using larger sample size, and different variables in determining depression.